Tislelizumab plus chemotherapy is more cost-effective than chemotherapy alone as first-line therapy for advanced non-squamous non-small cell lung cancer - Liang, Xueyan; Chen, Xiaoyu; Li, Huijuan; Li, Yan (Frontiers in Public Health, 2023)
Background and objective Tislelizumab is a programmed cell death protein-1 (PD-1) inhibitor. Tislelizumab plus chemotherapy as first-line option for advanced non-squamous non-small cell lung cancer (NSCLC), compared with chemotherapy alone, resulted in significantly prolonged survival outcomes; however, evidence regarding its relative efficacy and cost is lacking. We aimed to evaluate the cost-effectiveness of tislelizumab plus chemotherapy compared with that of chemotherapy alone, from the health care perspective in China. Methods A partitioned survival model (PSM) was used for this study. The survival data were obtained from the RATIONALE 304 trial. Cost-effectiveness was defined as incremental cost-effectiveness ratio (ICER) less than the willingness to pay (WTP) threshold. Incremental net health benefits (INHB), incremental net monetary benefits (INMB), and subgroup analyses were also assessed. Sensitivity analyses were further established to assess the model stability. Results Compared with chemotherapy alone, tislelizumab plus chemotherapy increased by 0.64 quality-adjusted life-years (QALYs) and 1.48 life-years, and yielded an increase of 16,631 in cost per patient. The INMB and INHB were 7,510 and 0.20 QALYs at a WTP threshold of 38,017/QALY, respectively. The ICER was 26,162/QALY. The outcomes were most sensitive to the HR of OS for tislelizumab plus chemotherapy arm. The probability of tislelizumab plus chemotherapy being considered cost-effective was 87.66% and >50% in most of the subgroups at the WTP threshold of 38,017/QALY. At the WTP threshold of 86,376/QALY, the probability achieved 99.81%. Furthermore, the probability of tislelizumab plus chemotherapy being considered cost-effective in subgroups of patients with liver metastases and PD–L1 expression ≥50% were 90.61 and 94.35%, respectively. Conclusion Tislelizumab plus chemotherapy is likely to be cost-effective as a first-line treatment for advanced non-squamous NSCLC in China.